1988
DOI: 10.1128/aem.54.12.3122-3125.1988
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nontuberculous mycobacteria in water supplies of hemodialysis centers

Abstract: Infection of hemodialysis patients with nontuberculous mycobacteria (NTM) has been associated with water used in reprocessing hemodialyzers. This study was conducted to determine the prevalence of NTM and other bacteria in water samples collected over a 13-week period from 115 randomly selected dialysis centers in the United States. Total viable counts were determined by membrane filter assays; increased recovery of NTM was obtained by dosing a portion of each water sample with 1% formaldehyde (HCHO) before fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 16 publications
(14 reference statements)
1
41
0
4
Order By: Relevance
“…Carson et al (36) found that strains of Mycobacterium chelonei cultured in commercial distilled water showed survivors in 2% aqueous formaldehyde (HCHO) solutions up to 24 hours, and they postulated that a higher concentration of HCHO was needed for effective killing of nontuberculous mycobacteria. Ultimately Carson et al (37) recommended 4% formaldehyde for effective killing of nontuberculous mycobacteria at room temperature. On the other hand, Hakim et al (38) warned that the use of 4% formaldehyde may be associated with a significant increase in residual formaldehyde, which may be infused into the patient.…”
Section: Inadequate Concentration Of Disinfectantsmentioning
confidence: 99%
“…Carson et al (36) found that strains of Mycobacterium chelonei cultured in commercial distilled water showed survivors in 2% aqueous formaldehyde (HCHO) solutions up to 24 hours, and they postulated that a higher concentration of HCHO was needed for effective killing of nontuberculous mycobacteria. Ultimately Carson et al (37) recommended 4% formaldehyde for effective killing of nontuberculous mycobacteria at room temperature. On the other hand, Hakim et al (38) warned that the use of 4% formaldehyde may be associated with a significant increase in residual formaldehyde, which may be infused into the patient.…”
Section: Inadequate Concentration Of Disinfectantsmentioning
confidence: 99%
“…A survey across the USA found that nontuberculous mycobacteria, including M. abscessus, were recovered from 83% of water supplies to dialysis units. 11 This led others to conclude that the effectiveness of dialyser disinfection is critically important, particularly given the increased susceptibility of dialysis patients to infection. 12 There have been reports of M. abscessus infections in patients with no known risk factors, 1,13 but with an incubation period estimated to be between 16 days and 2 years (mean 30 days) the source may be difficult to identify.…”
Section: Reportmentioning
confidence: 99%
“…The mycobacteria concentration in the environment is always lower than 10 3 CFU mL -1 , so we conducted assays using a mycobacteria concentration around 10 3 CFU mL -1 . 2,3,5 Literature reports that satisfactory disinfection is not always achieved with mycobacterium concentrations around 10 6 CFU mL -1 , probably because small · OH/bacteria ratios in the suspension usually culminate in a less efficient disinfection process. 39 Here, PEC treatment promoted 100% disinfection within 3 min, however, faster inactivation occurs with M. abscessus, within 1 min.…”
Section: Photoelectrocatalytic Disinfection Using Ti/ Tio Photoanodesmentioning
confidence: 99%
“…In fact, a study conducted in the USA demonstrated that the water from 95 hemodialysis centers (83%) was contaminated with microorganisms, and that 50% of the samples examined contained mycobacteria, including M. chelonae and M. fortuitum. 5 In general, rapid-growing mycobacteria are difficult to eradicate via common disinfection practices, compared with coliforms. 6 They are resistant to chlorination, which is used to treat swimming pool and drinking water; they also resist treatment with glutaraldehyde (GA), benzalkonium chloride, organomercury compounds, chlorohexidine, and even autoclavation.…”
Section: Introductionmentioning
confidence: 99%